Basal serum cortisol and adrenocorticotropic hormone levels in patients with atopic dermatitis - Zohreh Tehranchinia; Hoda Rahimi; Sara Lotfi (Mattioli1885, 2017)
Background: Certain studies suggest that percutaneous absorption of topical steroids may cause suppression of hypothalamic-pituitary-adrenal axis (HPAA) in atopic dermatitis (AD) patients. This study aimed to investigate the basal serum cortisol, adrenocorticotropic hormone (ACTH), and IgE levels in patients with AD and their correlation with the disease severity. Methods: Levels of basal serum cortisol, ACTH, and IgE were assessed by ELISA in 31 patients with AD and 31 controls. Clinical severity of AD was evaluated by the scoring of atopic dermatitis (SCORAD) index. Results: No statistical difference was observed between the two groups for basal serum cortisol and ACTH levels. The serum IgE level was significantly higher in the AD group. The SCORAD index was correlated with serum IgE level. Conclusions: Basal serum cortisol and ACTH levels are normal in AD patients. Serum IgE level is significantly higher in AD patients and is correlated with the disease severity.